Effects of single residue substitution at N-terminal region of L2 lipase towards its temperature stability and activity - Bukhari @ Albukhri, Noramirah (2020)
Enzymes as biocatalyst have been engineered to suit the extreme conditions of industrial processes. In a previous C-terminal region study to improve temperature stability, a single residue substitution enhanced the stability and activity of L2 lipase. However, the role of the N-terminal region of L2 towards stability and activity remained unexplored. Thus, this study aimed to determine the effects of single residue substitution at a critical point of the N-terminal region of L2 lipase towards its temperature stability and activity through in silico approach and experimental characterisations. Prediction software was employed to predict the critical point and stability changes upon residue substitution. Position Ala8 was chosen as the critical point and substituted with valine (V), proline (P) and glutamic acid (E). Molecular dynamics simulation was used to analyse the stability changes in the mutant lipases. The results showed mutant lipase A8E was the most stable, followed by lipases A8P, wildtype L2 (wt-L2) and A8V. Substrate docking of wt-L2 and mutant lipases showed only slight differences in binding affinity. Site-directed mutagenesis was then employed to construct the mutant lipases, which expressed the enzymes, subsequently purified for characterisation. The optimum temperature of the mutant lipases remained the same as wt-L2 at 70 °C, but A8V showed higher activity compared to wt-L2 lipase. All mutant lipases showed an improvement in thermostability, especially A8V that was able to retain 84 % residual activity after 30 min pre-incubation at 70 °C compared to 55 % by that of wt-L2. A8P showed half-life at 12 h compared to wt-L2 at 8 h at 60 °C. A8E (73.59 °C) showed the highest thermal denaturation point followed by A8V (70.68 °C) and A8P (70.19 °C). Secondary structure analysis showed wt-L2 had a higher composition of α-helix compared to mutant lipases. The optimum pH had shifted from pH 9.0 in wt-L2 to pH 8.0 in A8V and A8P. A8E was optimal at pH 7.0. Similarly, the pH stability of mutants has broadened in range (pH 6.0 to 10.0) compared to wt-L2 (pH 8.0 to 10.0). All mutant and wt-L2 lipases showed a preference in substrate p-nitrophenol decanoate, but with different catalytic efficiency. A8V (260.57 s-1/mM) was most efficient, followed by wt-L2 (162.43 s-1/mM), A8P (94.93 s-1/mM) and A8E (27.23 s-1/mM). In conclusion, substitution at the N-terminal region enhanced the activity of A8V and improved the stability of all mutants compared to wt-L2, suggesting that the N-terminal region influences the characteristics of L2 lipase.